2019
DOI: 10.3390/su11041146
|View full text |Cite
|
Sign up to set email alerts
|

Change in Characteristics of Soil Carbon and Nitrogen during the Succession of Nitraria Tangutorum in an Arid Desert Area

Abstract: The shrub Nitraria tangutorum is distributed widely in arid desert areas, and plays a critical role in the desert–oasis ecosystem. This study quantified varying characteristics of carbon (C) and nitrogen (N) in the soil at four stages—the initial stage (IS), stable stage (SS), degradation stage (DS), and severe degradation stage (SDS)—in a steppe ecosystem in the desert of northwestern China. The results indicated that N. tangutorum experienced both expansion and deterioration as a decline of 50.7% occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Yet, the vegetation coverage ranged from 14.3 to 43.8% at different successional stages, thus leading to the N. tangutorum nebkhas being in a mounded state at other successional stages, whereas the N. tangutorum nebkhas being in a wind erosion state at DEG, and the size of N. tangutorum nebkhas decreases and finally disappears. Several previous studies have found that large nebkhas can conserve and increase soil moisture and nutrient content which stimulated the growth and activity of soil microorganisms, and promoted plant growth [14,20,45]. In this study, the length of new branch showed an increase, then decreasing trend with N. tangutorum nebkhas succession, indicating that in RUD and EDV, wind-deposited sand accumulated among roots, growing shoots, and shoots of N. tangutorum, thus driving the development of N. tangutorum nebkhas.…”
Section: The Morphology and Development Of Shrub Determines The Succe...mentioning
confidence: 99%
“…Yet, the vegetation coverage ranged from 14.3 to 43.8% at different successional stages, thus leading to the N. tangutorum nebkhas being in a mounded state at other successional stages, whereas the N. tangutorum nebkhas being in a wind erosion state at DEG, and the size of N. tangutorum nebkhas decreases and finally disappears. Several previous studies have found that large nebkhas can conserve and increase soil moisture and nutrient content which stimulated the growth and activity of soil microorganisms, and promoted plant growth [14,20,45]. In this study, the length of new branch showed an increase, then decreasing trend with N. tangutorum nebkhas succession, indicating that in RUD and EDV, wind-deposited sand accumulated among roots, growing shoots, and shoots of N. tangutorum, thus driving the development of N. tangutorum nebkhas.…”
Section: The Morphology and Development Of Shrub Determines The Succe...mentioning
confidence: 99%
“…E. angustifolia belongs to the Elaeagnus genus in the Elaeagnaceae family. N. tangutorum and E. angustifolia are dominant halophytes in the Minqin Oasis; both of them are best known for excellent tolerance to salt and form the primary ecological barrier for that area [36,37]. However, both could not grow normally when salinity concentration exceeds 300 mM NaCl [39,40].…”
Section: Plant Materialsmentioning
confidence: 99%
“…are the dominant halophytes that are widespread in the saline area in arid and semi-arid regions of northwestern China [34]. Both also play important roles in the restoration of saline land and the main-tenance of ecological balance in the saline desert ecosystem of the Minqin Oasis [35][36][37]. Although both halophytic species could reduce the damage induced by osmotic stress and ionic stress in saline soils via various strategies, the inhibition of seed germination and seedling growth occurs when salinity concentration exceeds their respective salt-tolerant thresholds in the Minqin Oasis.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, most of the C substrate is distributed in the topsoil and litterfall layer. (Hu et al, 2008;Jobbagy and Jackson, 2001;Lal, 2009;Wang et al, 2019). For regulating the carbon and nutrient cycle, litterfall decomposition plays a vital role.…”
Section: Introductionmentioning
confidence: 99%